Letter : Goods for Spanish refugees - Schevenels, Walther, b. 1894
032-0041-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, Avenue d'Orsay, Paris-VIIe Sch/T Your Reference: WMC/FAB TELEGRAMS: INTERFED—PARIS TELEPHONE: INVALIDES 45-88 AFFILIATED COUNTRIES: ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DANTZIG DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA EXECUTIVE COMMITTEE: President W. M. Citrine, Great Britain; Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; Corn. Mertens, Belgium; R. Tayerle, Czechoslovakia; General Secretary: W. Schevenels. Letter: F.I. de Sol No. 764 1st June, 1939. Sir Walter M. Citrine, Trades Union Congress, Transport House, Smith Square, London, S.W.1. Dear Comrade Citrine, Goods for Spanish Refugees. I duly received your letter of the 26th May and have given the necessary instructions to the Co-operative Wholesale Society in Rouen. Yours sincerely, W. Schevenels. General Secretary. 292/946/32/41